Atomic Fabrication of 2D Materials Using Electron Beams Inside an Electron Microscope - Mingrui Zhou; Wei Zhang; Jinyi Sun; Fuqiang Chu; Guocai Dong; Meng Nie; Tao Xu; Litao Sun (Nanomaterials)
Two-dimensional (2D) materials have garnered increasing attention due to their unusual properties and significant potential applications in electronic devices. However, the performance of these devices is closely related to the atomic structure of the material, which can be influenced through manipulation and fabrication at the atomic scale. Transmission electron microscopes (TEMs) and scanning TEMs (STEMs) provide an attractive platform for investigating atomic fabrication due to their ability to trigger and monitor structural evolution at the atomic scale using electron beams. Furthermore, the accuracy and consistency of atomic fabrication can be enhanced with an automated approach. In this paper, we briefly introduce the effect of electron beam irradiation and then discuss the atomic structure evolution that it can induced. Subsequently, the use of electron beams for achieving desired structures and patterns in a controllable manner is reviewed. Finally, the challenges and opportunities of atomic fabrication on 2D materials inside an electron microscope are discussed.